Growth performance and meat quality of broiler chickens supplemented with chicken-specific Lactobacillus CSL-13 in drinking water - LV, LE; YAN, HIA; LIU, XIAOLU; XU, QIANQIAN; YIN, CHUNHUA (The Indian Journal of Animal Sciences, 2012)
Effect of chicken-specific Lactobacillus CSL-13 isolated from the digestive tract of chickens on the growth performance and meat quality of broiler chickens was investigated. 1-day-old AA broiler chicks (900) were randomly allocated into 3 treatment groups with 3 replicates for raising over 42 days. Chicks of control group 1 were fed the basal diets that did not supplemented with CSL-13. The chicks of groups 2 and 3 were fed the basal diets same to that of group 1, but supplemented with 1 and 2 ml of CSL-13 for each in feed water per day, respectively. The results indicated that the body weight (BW), average daily weight and feed conversion rate (FCR) were all significantly (P < 0.05) increased by the dietary inclusion of CSL-13. The birds fed with the level of CSL-13 of 2 ml exhibited the highest BW and FCR, however there was no significant difference in mortality rate among different groups. Additionally, CSL-13 is giving a contribution towards an improvement of the chemical, nutritional and sensorial characteristics of breast fillet. Improved protein and free amino acid contents, and decreased fat content in chicken breast fillet (P < 0.05), were detected in birds by the supplement of CSL-13 in drinking water. Meanwhile, improvement in sensory attributes was also noticed in broilers fed with CSL-13. So chicken-specific CSL-13 can be used as a growth promoter and meat quality enhancer on broiler poultry.